Porous perovskite catalyst for efficient electrocatalytic reduction of CO2 and preparation method thereof

The preparation of porous perovskite catalysts by lyophilization and co-precipitation methods solves the problems of small specific surface area and complex process of traditional perovskite catalysts, and achieves efficient CO2 electrocatalytic reduction and oxygen reduction reaction activities.

CN119553299APending Publication Date: 2025-03-04JINAN CHENGYAN GUONENG ZHONGCHENG ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411747303.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The specific surface area of ​​traditional perovskite catalysts is low, which limits the adsorption and transport of CO2 on the catalyst surface, resulting in poor catalytic effect, and the traditional template method has complex and unenvironmental processes.

Method used

The porous perovskite catalyst is prepared by lyophilized drying and co-precipitation method. By controlling the concentration of the metal nitrate solution and the selection of precipitant agent, a catalyst with a larger specific surface area and a more ordered pore structure is formed.

Benefits of technology

The specific surface area and pore structure of the catalyst are improved, the adsorption and transport capacity of CO2 are significantly improved, the oxygen reduction reaction activity is enhanced, and the problem of slow electrocatalytic reduction kinetics of CO2 is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553299A_ABST
    Figure CN119553299A_ABST
Patent Text Reader

Abstract

The invention relates to a porous perovskite catalyst for efficient electrocatalytic reduction of CO2 and a preparation method thereof, the structural general formula of the catalyst is La1-xSrxFe1-yMnyO3-alpha, 0 < = x < = 1, and 0 < y < = 1; according to the composite perovskite oxide, a high-activity porous perovskite catalyst suitable for an electrocatalytic reduction CO2 reaction is designed through a chemical cutting mode according to the characteristics of a chemical reaction. The preparation method comprises the following steps: firstly, preparing a precursor solution by taking metal nitrate as a raw material, then carrying out coprecipitation by taking ammonia water or ammonium carbonate as a precipitator, freezing by liquid nitrogen, drying by a vacuum freeze dryer, and roasting to obtain the porous perovskite powder. The catalyst has the advantages of environmental friendliness, low cost, simplicity in preparation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high-activity catalysts for CO2 catalytic reduction, and specifically relates to a porous perovskite catalyst for high-efficiency electrocatalytic reduction of CO2 and a preparation method thereof. Background Art

[0002] Under the general background of the country's efforts to achieve the goals of "carbon peak" and "carbon neutrality", the resource utilization of CO2 has become one of the necessary ways to quickly achieve the dual carbon goals. At present, the research on CO2 resource utilization technology is mainly focused on the three aspects of photocatalytic reduction of CO2, electrocatalytic reduction of CO2, and thermal catalytic reduction of CO2. Among them, the electrocatalytic reduction of CO2 stands out in the field of CO2 resource utilization technology due to its mild experimental conditions and high reaction activity. However, due to the highly oxidizing nature of CO2, it has a high chemical stability. In addition, the reduction process of CO2 is also challenged by competitive hydrogen evolution reactions and has high thermodynamic and kinetic barriers. Therefore, the design and development of highly active catalysts is the key to efficient electrocatalytic reduction of CO2, and it has also been the focus of research by many researchers in recent years.

[0003] Perovskite oxides are expected to be a potential alternative to precious metal catalysts due to their adjustable composition, low cost, and strong structure-activity relationship. However, the specific surface area of ​​traditional perovskite catalysts (<10m 3 / g) is low. In the field of catalysis, the specific surface area greatly affects the activity of the catalyst. The specific surface area and pore size of the perovskite catalyst prepared by the traditional coprecipitation method, sol-gel method and hydrothermal method are small, and the exposed active sites are few, which limits the adsorption of CO2 on the catalyst surface, and it is difficult to provide an efficient channel for the transmission of CO2, so that the catalyst cannot achieve a satisfactory catalytic effect; while the specific surface area of ​​the perovskite catalyst prepared by the traditional template method is improved, but the method is complex and has low environmental friendliness. For example, the PMMA template method uses methyl methacrylate, a synthetic monomer of PMMA (polymethyl methacrylate), and dibenzoyl peroxide, an initiator, which are both toxic. To this end, the present invention provides a porous perovskite catalyst for efficient electrocatalytic reduction of CO2 and a preparation method thereof. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention proposes a porous perovskite catalyst for efficient electrocatalytic reduction of CO2 and a preparation method thereof.

[0005] To achieve the above purpose, the technical solution provided by the present invention is:

[0006] A method for preparing a porous perovskite catalyst for efficient electrocatalytic reduction of CO2, characterized in that it comprises the following steps:

[0007] 1) According to La 1-x Srx Fe 1-y Mn y O 3-α According to the stoichiometric ratio, the corresponding metal nitrates (lanthanum nitrate, strontium nitrate, manganese nitrate, and iron nitrate) are weighed and dispersed in deionized water to form respective metal nitrate solutions, and then the respective metal nitrate solutions are mixed and stirred evenly to obtain a precursor solution; wherein, 0≤x≤1, 0<y≤1, and the molar concentration of the metal nitrate in each metal nitrate solution is 1-1.5M. If the concentration is too low, the induction period of the grains is longer, the grain size is larger, and the specific surface area is smaller; while if the concentration is too high, the nucleation speed is faster, the grains are more, the grains are easy to aggregate and grow in a limited space, the specific surface area is small, and the catalytic activity is poor. When the concentration is controlled at 1-1.5M, a precipitate of suitable grain size can be obtained, which is beneficial to improving the phase of the target product;

[0008] 2) adding an excess amount of precipitant to the precursor solution obtained in step 1), sealing and allowing to react, and after the reaction is completed, freezing the product in liquid nitrogen (-196° C.), followed by freeze drying, and grinding (grinding until no obvious particles are present) to obtain a precursor powder;

[0009] The precipitant is ammonia water or ammonium carbonate with a molar concentration of 0.5-1.5M. The present invention selects ammonia water or ammonium carbonate as the precipitant because such substances are volatile or easy to decompose, and even if there is any residue, it can be removed through the subsequent roasting process; while other precipitants such as hydroxide precipitants will have metal cation residues, which is not conducive to the quality of the final product;

[0010] 3) The precursor powder obtained in step 2) is placed in a high-temperature tube furnace (which can stably control the air flow rate, which is conducive to product formation) and calcined in an air atmosphere. After naturally cooling to room temperature, a porous perovskite oxide is obtained.

[0011] Furthermore, the amount of ammonia water or ammonium carbonate added is 1.5 to 2.0 times the molar amount required to precipitate all metal nitrates, and the mixture is sealed and allowed to react for 12 to 24 hours to ensure that all metal cations are completely precipitated and the cation ratio perfectly meets the ratio required by the structural formula.

[0012] Furthermore, in step 2), the liquid nitrogen freezing time is 15 to 30 minutes, which can quickly freeze the precipitate to below the freezing point; freeze drying is carried out in a vacuum freeze dryer at a temperature of -65°C for 24 to 72 hours, and the ice is converted into vapor under vacuum and removed, and the remaining gaps can form porous structures.

[0013] Further, step 3) is specifically as follows:

[0014] The precursor powder obtained in step 2) is placed in a high-temperature tubular furnace with an air intake flow rate of 30 to 50 ml / min (if the air flow rate is too large and the air content is too high, the roasting process will rapidly oxidize and release heat, resulting in catalyst sintering, pore collapse, and a reduction in specific surface area; if the air flow rate is too small, it will affect the speed of catalyst phase formation; therefore, controlling the air intake flow rate within this range can ensure that the composite metal oxide will not have an adverse effect on the catalyst phase formation during the phase formation process due to excessive or insufficient air flow), roast at 600 to 800°C for 2 to 6 hours, and naturally cool to room temperature to obtain a porous perovskite oxide.

[0015] In addition, the present invention also provides a porous perovskite catalyst prepared by the above method, the general structural formula of which is: La 1-x Sr x Fe 1-y Mn y O 3-α ; wherein, 0≤x≤1, 0<y≤1; the catalyst is a cubic ABO3-type porous perovskite, wherein the A position is lanthanum and / or strontium, and the B position is manganese or iron and manganese; the composite perovskite oxide is designed according to the characteristics of the chemical reaction by chemical tailoring (specifically, the amount of La and Sr in the A-position elements and the amount of Fe and Mn in the B-position elements can be controlled, that is, the valence state, proportion, and oxygen vacancy content of the elements can be adjusted over a wide range) to obtain a highly active porous perovskite oxide catalyst suitable for the electrocatalytic reduction of CO2 reaction, which has a more ordered pore structure and a larger specific surface area, and can exhibit excellent ORR (oxygen reduction) reaction activity.

[0016] At the same time, the present invention also provides a method for highly efficient electrocatalytic reduction of CO2, the special feature of which is that the above-mentioned porous perovskite oxide is used as a catalyst.

[0017] The advantages of the present invention are:

[0018] 1. The present invention adopts the method of freeze drying and co-precipitation to prepare a porous perovskite catalyst with a large specific surface area. The process of freeze drying to obtain a porous material is relatively simple and is carried out at low temperature and low pressure. In addition, the water can be directly sublimated, the material is completely dehydrated, and the dried sample is very stable and convenient for long-term storage. Since the material is dried in a frozen state, compared with other drying methods, the physical structure and molecular structure of the material change very little, and its organizational structure and appearance are well preserved.

[0019] 2. Compared with the perovskite catalyst prepared by the conventional co-precipitation method, the porous perovskite catalyst prepared by the present invention has a more ordered pore structure and a larger specific surface area, which is up to 4 times that of the ordinary structure; compared with the existing template method for preparing perovskite catalysts, the process flow is simpler and the preparation process is more environmentally friendly.

[0020] 3. The raw material cost of the present invention is low and easy to prepare on a large scale. The specific surface area of ​​the perovskite catalyst is increased by obtaining a porous structure, thereby increasing the adsorption and transmission capacity of CO2 on the catalyst, showing better ORR reaction activity and solving the problem of slow CO2 electrocatalytic reduction kinetics. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The SEM images of the catalysts prepared in Comparative Example 1 and Example 1; a is Comparative Example 1, and b is Example 1;

[0022] Figure 2 N2 adsorption-desorption isotherms and pore size distribution diagrams of the catalysts prepared in Comparative Example 1 and Example 1; a and c are respectively N2 adsorption-desorption isotherms and pore size distribution diagrams of the catalyst in Comparative Example 1, and b and d are respectively N2 adsorption-desorption isotherms and pore size distribution diagrams of the catalyst in Example 1;

[0023] Figure 3 The ORR activity diagram of the catalysts prepared in Comparative Example 1 and Example 1;

[0024] Figure 4 ORR activity diagram of the catalysts prepared in Example 2 and Example 3. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:

[0026] Comparative Example 1

[0027] Preparation of common structure La 0.75 Sr 0.25 Mn 0.5 Fe 0.5 O 3-α Catalyst, the steps are as follows:

[0028] Lanthanum nitrate (0.075 mol), strontium nitrate (0.025 mol), manganese nitrate (0.05 mol) and iron nitrate (0.05 mol) were dispersed in deionized water at a molar concentration of 1.5 M to obtain metal nitrate solutions, and then the metal nitrate solutions were mixed and stirred to obtain a precursor solution; an excess of 1.5 times the amount of ammonia required for the precipitation of lanthanum, strontium, manganese and iron metal ions was added to the precursor solution, and the mixture was sealed and allowed to stand for 12 hours, filtered and dried in a forced air drying oven for 12 hours, ground and placed in a high-temperature tube furnace in an air atmosphere (40 ml / min) and calcined at 700 ° C for 4 hours to obtain a common structure La 0.75 Sr 0.25 Mn 0.5 Fe 0.5O 3-α catalyst.

[0029] Example 1

[0030] Preparation of porous structure La 0.75 Sr 0.25 Mn 0.5 Fe 0.5 O 3-α Catalyst, the steps are as follows:

[0031] Lanthanum nitrate (0.075 mol), strontium nitrate (0.025 mol), manganese nitrate (0.05 mol) and iron nitrate (0.05 mol) were dispersed in deionized water according to the molar concentration of 1.5 M to obtain metal nitrate solutions, and then the metal nitrate solutions were mixed and stirred to obtain a precursor solution; 1.5 times the amount of ammonia water required for the precipitation of lanthanum, strontium, manganese and iron metal ions was added to the above precursor solution, and the solution was sealed and allowed to stand for 12 hours, and then first frozen in -196°C liquid nitrogen for 15 minutes, and then placed in a -65°C vacuum freeze dryer for freeze drying for 48 hours, and after drying, ground and placed in a high-temperature tube furnace in an air atmosphere (40 ml / min) at 700°C for 4 hours to obtain a porous structure La 0.75 Sr 0.25 Mn 0.5 Fe 0.5 O 3-α catalyst.

[0032] Example 2

[0033] Preparation of porous LaMnO 3-α Catalyst, the steps are as follows:

[0034] Lanthanum nitrate (0.1 mol) and manganese nitrate (0.1 mol) were dispersed in deionized water at a molar concentration of 1 M to obtain metal nitrate solutions, and then the metal nitrate solutions were mixed and stirred to obtain a precursor solution; an excess amount of ammonia water of 1.8 times the amount of ammonia water required for precipitating lanthanum and manganese metal ions was added to the above precursor solution, and the solution was sealed and allowed to stand for 24 hours, and then first frozen in liquid nitrogen at -196°C for 30 minutes, and then placed in a vacuum freeze dryer at -65°C for freeze drying for 72 hours, and after drying, ground and placed in a high-temperature tube furnace in an air atmosphere (50 ml / min) at 600°C for 6 hours to obtain a porous structure LaMnO 3-α catalyst.

[0035] Example 3

[0036] Preparation of porous SrFe 0.25 Mn 0.75 O 3-α Catalyst, the steps are as follows:

[0037] According to the standard of molar concentration of 1.2M, strontium nitrate (0.1mol), manganese nitrate (0.0025mol) and iron nitrate (0.075mol) were dispersed in deionized water to obtain metal nitrate solutions, and then the metal nitrate solutions were mixed and stirred to obtain a precursor solution; 2.0 times the amount of ammonia water required for the precipitation of strontium, manganese and iron metal ions was added to the above precursor solution, sealed and allowed to stand for 18 hours, and then first frozen in -196℃ liquid nitrogen for 20min, and then placed in a -65℃ vacuum freeze dryer for freeze drying for 24h, and after drying, ground and placed in a high-temperature tube furnace in an air atmosphere (30ml / min) at 800℃ for 2h to obtain a porous structure SrFe 0.25 Mn 0.75 O 3-α catalyst.

[0038] In order to verify the performance of the porous perovskite catalyst prepared by the method of the present invention, the products prepared in Comparative Example 1 and Example 1 were also subjected to the following tests:

[0039] 1. Field emission scanning electron microscopy to determine the microstructure of perovskite catalysts:

[0040] The porous perovskite catalysts (La 0.75 Sr 0.25 Mn 0.5 Fe 0.5 O 3-α ) Field emission scanning electron microscope (FESEM (Carl Zeiss) SIGMA 500) was used to measure its microstructure. The test results are shown in Figure 1 shown.

[0041] from Figure 1 It can be seen that the perovskite catalyst La prepared by the preparation method of the present invention 0.75 Sr 0.25 Mn 0.5 Fe 0.5 O 3-α The smaller particle size and more porous structure are presented, which is mainly attributed to the fact that when the sample is prepared by freeze-drying, the water directly sublimates and expands, leaving voids in the material and creating more porous structure.

[0042] 2. Physical adsorption instrument tests the specific surface area of ​​catalyst materials

[0043] The titanium ore type catalyst (La 0.75 Sr 0.25 Mn 0.5 Fe 0.5 O 3-α) The N2 adsorption-desorption isotherm, specific surface area and pore size distribution of the material were tested using Quantachrome Instruments NOVA2200e specific surface area analyzer. The test results are as follows: Figure 2 shown.

[0044] Figure 2 The N2 adsorption-desorption isotherms (a and b) and pore size distributions (c and d) of Comparative Example 1 (a and c) and Example 1 (b and d) are compared. As can be seen from the figure, the specific surface area of ​​the porous perovskite catalyst prepared by the preparation method of the present invention is as high as 37.466 m 2 / g, which is about the same as the common structure perovskite catalyst (9.225m 2 / g) 4 times the specific surface area ( Figure 2 a and c), the pore volume is 0.1686 cm 3 / g, relative to the pore volume of common structure perovskite catalyst (0.07650cm 3 / g) is 2.2 times ( Figure 2 b and d).

[0045] The catalysts prepared in Comparative Example 1, Example 1, Example 2 and Example 3 were subjected to the following oxygen reduction activity test:

[0046] The ORR performance of the catalyst was tested on a CHI-760E electrochemical workstation using linear sweep voltammetry (LSV). Before testing the ORR performance, oxygen was passed into the 0.1 M KOH electrolyte for 30 minutes to saturate the gas in the electrolyte. The ORR and OER potentials were set to 0.2-1.2 V, and the scan rate was set to 5 mV·s -1 , the test results are as follows Figure 3 and 4 shown.

[0047] from Figure 3 It can be seen that the half-wave potential of Comparative Example 1 and Example 1 increases from 0.660 V of Comparative Example 1 to 0.754 V of Example 1. The increase in the onset potential and half-wave potential of the perovskite catalyst indicates that the acquisition of a porous structure can enhance the ORR activity of the catalyst. Figure 3 and Figure 4 The porous perovskite catalyst prepared by the present invention exhibits high electrocatalytic reduction activity.

Claims

1. A method for preparing a porous perovskite catalyst for efficient electrocatalytic reduction of CO2, characterized in that: The following steps are involved: 1) According to La 1-x Sr x Fe 1-y Mn y O 3-α According to the stoichiometric ratio, the corresponding metal nitrates are weighed and dispersed in deionized water to form respective metal nitrate solutions, and then the respective metal nitrate solutions are mixed and stirred to obtain a precursor solution; wherein 0≤x≤1, 0<y≤1, and the molar concentration of the metal nitrate in each metal nitrate solution is 1 to 1.5M; 2) adding an excess amount of precipitant to the precursor solution obtained in step 1), sealing and allowing to react, and after the reaction is completed, freezing the product in liquid nitrogen, followed by freeze drying, and grinding to obtain a precursor powder; The precipitant is ammonia water or ammonium carbonate with a molar concentration of 0.5-1.5M; 3) The precursor powder obtained in step 2) is placed in a high-temperature tube furnace and calcined in an air atmosphere. After the powder naturally cools to room temperature, a porous perovskite oxide is obtained.

2. The method for preparing the porous perovskite catalyst according to claim 1, characterized in that: In step 2), the amount of ammonia water or ammonium carbonate added is 1.5 to 2.0 times the molar amount required to precipitate all metal nitrates; The sealed container is allowed to react for 12 to 24 hours.

3. The method for preparing the porous perovskite catalyst according to claim 2, characterized in that: In step 2), the liquid nitrogen freezing time is 15 to 30 minutes; Freeze drying is carried out in a vacuum freeze dryer at a temperature of -65°C for 24 to 72 hours.

4. The method for preparing the porous perovskite catalyst according to claim 3, characterized in that: Step 3) is specifically: The precursor powder obtained in step 2) is placed in a high-temperature tube furnace with an air intake flow rate of 30 to 50 ml / min, and is calcined at 600 to 800° C. for 2 to 6 hours. After naturally cooling to room temperature, a porous perovskite oxide is obtained.

5. The method for preparing the porous perovskite catalyst according to claim 4, characterized in that: In step 3), the heating rate of the high temperature tube furnace is 10°C / min.

6. A porous perovskite catalyst for efficient electrocatalytic reduction of CO2, characterized in that: The method is prepared by any one of claims 1 to 5.

7. A method for efficient electrocatalytic reduction of CO2, characterized in that: The porous perovskite catalyst according to claim 6 is used.